Akuntabilitas dan Transparansi Pengelolaan Anggaran Pendaptan dan Belanja Nagari Pasilihan Kecamatan X Koto Diatas Kabupaten Solok Tahun 2019 - Ahmadani Azhari; Yeni Melia (Jurnal Akuntansi Syariah (JAkSya), 2021)
Accountability and transparency of the management of the Pasilihan nagari budget for 2019 has become a concern since the nagari government received a large disbursement of funds compared to previous years. In carrying out the wheels of government, the Pasilihan nagari government has not yet been optimal in socializing and publishing reports on the realization of the nagari revenue and expenditure budget to the public. Based on Permendagri Number 113 of 2014 concerning village financial management, the fifth part of the accountability article 40 states that the budget realization report must be published to the public. The purpose of this study was to determine the Accountability and Transparency of the Management of the Pasilihan nagari Budget in 2019. The type of research used in this study was field research. The method used in this research is descriptive with a qualitative approach. The data collection technique that the writer uses in this research is through interviews and collecting documents. The results of the study indicate that the Pasilihan nagari government has implemented the principles of accountability and transparency in the management of APBNagari. In general, accountability and transparency have started to be implemented well. However, there are still some indicators of accountability and transparency standards or criteria that have not been implemented by the Pasilihan nagari government